광자 계수 집적 영상 현미경을 사용한 마이크로 물체의 3차원 시각화와 인식 - 조명진; 조기옥; 신동학; Cho, Myungjin; Cho, Giok; Shin, Donghak (한국정보통신학회논문지, 2015)
In this paper, we propose three-dimensional (3D) visualization and recognition techniques of micro-objects under photon-starved conditions using photon counting integral imaging microscopy. To capture high resolution 2D images with different perspectives in the proposed method, we use Synthetic Aperture Integral Imaging (SAII). Poisson distribution which is mathematical model of photon counting imaging system is used to extract photons from the images. To estimate 3D images with 2D photon counting images, the statistical estimation is used. Therefore, 3D images can be obtained and visualized without any damage under photon-starved conditions. In addition, 3D object recognition can be implemented using nonlinear correlation filters. To prove the usefulness of our technique, we implemented the optical experiment. 본 논문에서는 광자 계수 집적 영상 현미경을 사용하여 광자가 희박한 조건에서 마이크로 물체의 3차원 시각화와 인식에 대한 기술을 제안한다. 제안하는 방법에서는 고해상도의 서로 다른 원근감을 가지는 2차원 영상을 획득하기 위해 합성조리개 집적 영상을 사용한다. 그리고 영상으로부터 광자를 추출하기 위해 광자계수 영상 시스템의 수학적 모델인 포아송 분포를 사용하며 통계적 추정법으로 부터 3차원 영상을 추정한다. 따라서, 광자가 희박한 조건에서 마이크로 물체가 손상되지 않으면서 그에 대한 3차원 영상을 획득하고 시각화할 수 있다. 추가적으로, 비선형 상관 필터를 사용하여 3차원 물체의 인식도 가능하다. 본 기술의 유용성을 증명하기 위해, 광학적 실험을 수행하였다.